2002
DOI: 10.1128/jvi.76.15.7535-7543.2002
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Nef-Mediated HLA Class I Down-Regulation on Human Immunodeficiency Virus Type 1-Specific CD8+T-Cell Cytolytic Activity and Cytokine Production

Abstract: A previous study using a Nef-defective human immunodeficiency virus type 1 (HIV-1) mutant suggested that Nef-mediated down-regulation of HLA class I on the infected cell surface affects the cytolytic activity of HIV-1-specific cytotoxic T-lymphocyte (CTL) clones for HIV-1-infected primary CD4 ؉ T cells. We confirmed this effect by using a nef-mutant HIV-1 strain (NL-M20A) that expresses a Nef protein which does not induce down-regulation of HLA class I molecules but is otherwise functional. HIV-1-specific CTL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 47 publications
4
105
1
Order By: Relevance
“…Given the importance of HIV-1-specific CD8 + CTL in the control of disease (reviewed in [14]) and the role of MHC-I for presenting antigen to CTL, it is hypothesized that Nef mediates viral evasion of HIV-1 from immune control in vivo [15,16]. This hypothesis is supported by in vitro models that demonstrate Nef-mediated interference in clearance of HIV-1 by CTL [17][18][19]. These studies suggest that Nef allows HIV-1 to evade CTL by down-regulating MHC-I and by rendering infected cells relatively resistant to killing.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Given the importance of HIV-1-specific CD8 + CTL in the control of disease (reviewed in [14]) and the role of MHC-I for presenting antigen to CTL, it is hypothesized that Nef mediates viral evasion of HIV-1 from immune control in vivo [15,16]. This hypothesis is supported by in vitro models that demonstrate Nef-mediated interference in clearance of HIV-1 by CTL [17][18][19]. These studies suggest that Nef allows HIV-1 to evade CTL by down-regulating MHC-I and by rendering infected cells relatively resistant to killing.…”
Section: Introductionmentioning
confidence: 53%
“…Our subsequent study of inhibition of HIV-1 replication evaluated Nef that was physiologically expressed, but also compared virus containing Nef with deleted Nef [19]. Tomiyama et al [18] subsequently reported that a single point mutation in Nef ablating MHC-I down-regulation but not other functions (M20A) could affect the antiviral function of HIV-1-specific CTL, suggesting that MHC-I downregulation is necessary and sufficient. Our current study utilizes this mutation to evaluate the role of MHC-I down-regulation in the interaction of HIV-1 Nef and CTL, exploring the hypothesis that MHC-I down- Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Nef has been proposed to mediate resistance of HIV-1 to CTL by down-modulating class I molecules (6,8,9), we investigated whether escape of virus from Nef-specific CTL in vitro altered viral susceptibility to CTL of other specificities. The molecular clone HIV-1 NL4-3.1 was passaged under selective pressure in the presence of two Nef-specific CTL clones (KM3 and STD11, isolated from different infected individuals).…”
Section: Hiv-1 Escape From the Selective Pressure Of Nef-specific Ctlmentioning
confidence: 99%
“…Given the role of MHC-I in the function of CD8 ϩ CTL and the growing evidence that HIV-1-specific CTL are a determinant of immune control, it has been speculated that Nef potentiates persistence of HIV-1 in the face of the CTL response by down-regulating MHC-I to render infected cells less susceptible to clearance in vivo (6,8,9). In vitro studies have indicated that cells infected with Nef-containing virus are relatively resistant to cytolysis by CTL (6,9), and that replication of Nef-deleted virus is markedly more susceptible to inhibition by CTL than wild-type virus (8). These findings provide indirect evidence for the hypothesis that Nef contributes to the pathogenicity of HIV-1 infection by interfering with immunity against infected cells.…”
mentioning
confidence: 99%